California Mammals - Jameson, E. W.; Peeters, Hans J. (Berkeley, CA : University of California Press, 2020)
From river otters and minks to bobcats, pikas, and flying squirrels, California boasts a diverse and intriguing fauna. But many of these animals can be secretive, shy, and nocturnal and observing them in the wild can be difficult. During the past two decades, the first edition of this popular guide introduced thousands to California's mammals by describing techniques for recognizing their presence, and when possible, methods for watching them in their natural habitats. Mammals of California is now completely revised and updated throughout, making it an ideal companion in the field or classroom.
Frontmatter -- Dedication -- Contents -- Acknowledgments -- Mammal Ecology. STUDYING MAMMALS -- RARE AND ENDANGERED SPECIES -- REPRODUCTION -- SEASONAL DORMANCY -- SENSES -- MIGRATION AND MOVEMENTS -- MAMMALS AND CALIFORNIA SOCIETY -- FOOD OF MAMMALS -- Species Accounts. IDENTIFICATION OF MAMMALS -- MARSUPIALIA. -- INSECTIVORA. -- Moles (Talpidae) -- CHIROPTERA -- Leaf-nosed Bats (Phyllostomidae) -- Vesper Bats (Vespertilionidae) -- Free-tailed Bats (Molossidae) -- CARNIVORA -- Dogs, Foxes, and Allies (Canidae) -- Bears (Ursidae) -- Raccoons and Ringtails (Procyonidae) -- Weasels, Marten, and Allies (Mustelidae) -- Cats (Felidae) -- PINNIPEDIA -- Sea Lions or Eared Seals (Otariidae) -- Seals (Phocidae) -- Cetacea -- SPERM WHALES, DOLPHINS, AND PORPOISES (ODONTOCETI) -- Dolphins and Allies (Delphinidae) -- Porpoises (Phocoenidae) -- Sperm Whales (Physeteridae) -- Beaked Whales (Ziphiidae) -- Gray Whale (Eschrichtidae) -- Rorquals (Balaenopteridae) -- Right Whales (Balaenidae) -- PERISSODACTYLA. -- Pigs (Suidae) -- Deer (Cervidae) -- Sheep, Goats, and Cattle (Bovidae) -- RODENTIA -- Mountain Beaver (Aplodontidae) -- Squirrels (Sciuridae) -- Pocket Gophers (Geomyidae) -- Kangaroo Rats, Kangaroo Mice, and Pocket Mice (Heteromyidae) -- Beavers (Castoridae) -- Deer Mice, Wood Rats, and Allies (Cricetidae) -- Voles and Allies (Arvlcolidae)
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Okt 2020).
JSTOR
Keywords: Mammals -- California; Mammifères -- Californie; NATURE / Ecology; HISTORY / Indigenous Peoples of the Americas; Mammals; California